Cathelicidin‐related antimicrobial peptide alleviates alcoholic liver disease through inhibiting inflammasome activation - Li, Fengyuan; Zhao, Cuiqing; Shao, Tuo; Liu, Yunhuan; Gu, Zelin; Jiang, Mengwei; Li, Huimin; Zhang, Lihua; Gillevet, Patrick M; Puri, Puneet; Deng, Zhong‐Bin; Chen, Shao‐Yu; et al. (The Journal of pathology, 2020)
Alcoholic liver disease (ALD) is associated with gut dysbiosis and hepatic inflammasome activation. While it is known that antimicrobial peptides (AMPs) play a critical role in the regulation of bacterial homeostasis in ALD, the functional role of AMPs in the alcohol‐induced inflammasome activation is unclear. The aim of this study was to determine the effects of cathelicidin‐related antimicrobial peptide (CRAMP) on inflammasome activation in ALD. CRAMP knockout (Camp−/−) and wild‐type (WT) mice were subjected to binge‐on‐chronic alcohol feeding and synthetic CRAMP peptide was administered. Serum/plasma and hepatic tissue samples from human subjects with alcohol use disorder and/or alcoholic hepatitis were analyzed. CRAMP deficiency exacerbated ALD with enhanced inflammasome activation as shown by elevated serum interleukin (IL)‐1β levels. Although Camp−/− mice had comparable serum endotoxin levels compared to WT mice after alcohol feeding, hepatic lipopolysaccharide (LPS) binding protein (LBP) and cluster of differentiation (CD) 14 were increased. Serum levels of uric acid (UA), a Signal 2 molecule in inflammasome activation, were positively correlated with serum levels of IL‐1β in alcohol use disorder patients with ALD and were increased in Camp−/− mice fed alcohol. In vitro studies showed that CRAMP peptide inhibited LPS binding to macrophages and inflammasome activation stimulated by a combination of LPS and UA. Synthetic CRAMP peptide administration decreased serum UA and IL‐1β concentrations and rescued the liver from alcohol‐induced damage in both WT and Camp−/− mice. In summary, CRAMP exhibited a protective role against binge‐on‐chronic alcohol‐induced liver damage via regulation of inflammasome activation by decreasing LPS binding and UA production. CRAMP administration may represent a novel strategy for treating ALD. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.